Actualización del inventario de atractivos turísticos del cantón Bolívar, provincia de Manabí - Carranza Loor, Rosa Eliana (2012)
This work in Bolivar county, located in the province of Manabí aimed Update Inventory of Tourist Attractions of it, which brings out the reality of the natural and cultural attractions that turn in this way correcting the deficiencies presented and be able to give better handling and use. The scope of study was positive as it was supported by the tourism department of the canton and institutions including ESPAM MFL. Were surveyed a group of tourism experts, using the Delphi method, was analyzed each of the elements that make up the inventory of attractive chips, and a diagnosis was made of the information raised in the inventory of 2008. For the collection of information is visit the sites selected through field research, accompanied by a multidisciplinary team that evaluated the same each attraction. The methodology used was the application of the analytic-synthetic methods, and inductive and deductive. Finally we proceeded to fill the cards with the updated information. It will serve as the basis for different projects running in that district. Bolivar County has developed spontaneously, especially by the attractions of by category, type and subtype, through this document; we wish to provide guidance for submitting proposals is feasible considering the improvement of tourism canton and the region.